An Overview of Deep Learning Techniques on Chest X-Ray and CT Scan Identification of COVID-19 - Woan Ching Serena Low; Joon Huang Chuah; Clarence Augustine T. H. Tee; Shazia Anis; Muhammad Ali Shoaib; Amir Faisal; Azira Binti Khalil; Khin Wee Lai (Hindawi Publishing, 2024)
Indexed by WOS/Scopus/ERA